Hormone Receptors in Cervicovaginal Cells - Demirezen, Şayeste; Gerçeker, Funda; Beksaç, Sinan (Gynecology Obstetrics & Reproductive Medicine, 2013)
Some parts of the female reproductive system such as vagina and ectocervix is covered with stratified squamous epithelium (SSE). SSE consists of many layers and steroid hormones are essential for its normal growth and development. The steroid hormones mediate their effects via intracellular reseptors (3P). These are estrogen receptors, progesterone receptors and androgen receptors. These are found in cytoplasm or nucleus, or both. The steroid hormone receptors are made up of three functional domains: N-terminal domain (NTD), DNA binding domain (DBD) and ligand-binding domain (LBD). Initially, the steroid hormones diffuse into the cell and bind to its spesific receptor protein. Afterwards, hormone-bound receptor dimerizes with another receptor and then the dimer binds to specific DNA sequence through the DBD. Consequently, hormones regulate gene transcription via a direct interaction with DNA. In this review, we will give detailed information about SSE cells, hormone receptors, structure of the receptors and mechanism of their action.